The Importance of Being Honest: Free Spirits and Idiosyncrasy in Nietzsche - Zachary Stevens (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
The main argument of this paper is that the debate on whether Nietzsche is communitarian or individualist is wrongheaded, failing to distinguish the conception of community and individual Nietzsche critiques, the 'mob' and the 'Higher Man', from the conceptions Nietzsche envisions and hopes for, his 'free spirits' and – what I call, based on the critique of indivisible subjects in the Genealogy of Morality – the idiosyncrasy. I propose a reading of Nietzsche which elaborates his novel conception of a non-ascetic will to truth, based in courageous honesty and self-overcoming, rather than self-preservation, in order to conceive these individuals and communities. The coupling of Dionysus and Apollo has to be replaced with Dionysus and Ariadne because, using key terms from Deleuze's Nietzsche, the sense and value of critique is generated from a labyrinthine, Dionysian meaning as will to power and Ariadne's thread as evaluation based on the eternal recurrence, constituting the idiosyncrasy and the free spirits, respectively.